2014
DOI: 10.2527/jas.2013-6987
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water intake of grazing steers: The role of environmental factors controlling canopy wetness1

Abstract: Cattle obtain water primarily from the moisture in their feed and from drinking water. On pasture, the moisture content of the diet is influenced by plant tissue water (internal water) and surface moisture (external water), which may include dew, guttation, and intercepted rain, that influence the drinking water requirement. This study investigated the relationship between daily drinking water intake (DWI, L/d) of steers on pasture (19 steers with mean initial BW of approximately 400 kg) and soil and weather f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Highest water intake by the animals occurred from 9 to 12 h (0.62%) and from 18 to 21 h (0.46%), thus indicating that the animals drank more water in periods of high THI and h, and after greater consumption of forage. Therefore, the results corroborate Sun et al (2014), who reported that water intake is related to environmental temperature, air humidity, pasture moisture content, wind speed, solar radiation and dry matter intake.…”
Section: Resultssupporting
confidence: 90%
“…Highest water intake by the animals occurred from 9 to 12 h (0.62%) and from 18 to 21 h (0.46%), thus indicating that the animals drank more water in periods of high THI and h, and after greater consumption of forage. Therefore, the results corroborate Sun et al (2014), who reported that water intake is related to environmental temperature, air humidity, pasture moisture content, wind speed, solar radiation and dry matter intake.…”
Section: Resultssupporting
confidence: 90%
“…(iii) It influences the amount of water adhering to the leaves from dewrise. (iv) And thus, it also influences the drinking water demand of the animals 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Kohn model, drinking water was calculated by subtracting the other input fluxes from total water demand, which did not reflect the seasonal variation of drinking water intake. We used the models described by Cardot et al 28 for the stall period and Sun et al 15 for the grazing period to estimate drinking water intake as a function of ambient conditions (relative humidity, daily average temperature and precipitation), milk production, and soil water storage (during grazing). The Sun model was modified to consider the influence of body weight (an increase of 1 kg body weight causes 0.1 kg increase in drinking water 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations